ANALYSIS OF THE FACTORS OF SUCCESSFUL BREASTFEEDING OF INFANTS - Дячук, Анастасія; Мельничук, Лариса (SWorldJournal, 2024)
A survey was conducted using a form created by Google of 56 women with various types of breastfeeding. The questionnaire included questions about the woman’s age, social status, adherence to the breastfeeding support strategy, and problems at various sta